Variation of wood properties in a single stem of jack pine (Pinus banksiana Lamb.) - Feng, Nan (My University, 2002)
Radial and axial variation of tracheid length, relative density, ring width, radial and tangential shrinkage, and juvenile and mature wood volume were studied in a single stem of jack pine, 37 km north of Thunder Bay. The tree was 60-year-old and was from a naturally grown stand in the Jack Haggerty Forest of Lakehead University, Thunder Bay, Ontario. Specimens were taken from the tree stem at heights of 0.15, 1.4, 3.4, 5.4, 7.4, 9.4, 11.4, 13.4, 15.4 m along west and east aspect. Juvenile and mature wood boundary was demarcated by using the radial variation pattern of tracheid length as the criterion.Tracheid length increased from pith outward in the juvenile wood, reaching a maximum, then remained constant or leveled off towards the bark in the mature wood. The rate of increase in tracheid length with ring age increased with increasing height with an exception at 13.4 m. The mean tracheid length in the juvenile and mature wood increased from the base upward, reaching a maximum at 3.4 m and 5.4 m for the juvenile and mature wood, respectively, followed by a decrease further to the top. Relative density decreased from the pith outward with ring age in the juvenile wood and remained less variable in the mature wood, with an exception at 0.15 m. Relative density decreased with increasing height with an exception at 13.4 m in both juvenile and mature wood. Ring width increased with ring age from the pith outward in the juvenile wood and fluctuated in the mature wood. Ring width decreased with increasing height in the juvenile wood. No axial trend for ring width variation in the mature wood was found. Tangential shrinkage was greater than radial shrinkage. The mean tracheid length of the west aspect was significantly different from that o f the east aspect. Relative density of both juvenile and mature wood in the east aspect was significantly higher than that in the west aspect. Ring width in the west aspect was significantly wider than that in the east aspect for mature wood. For both tracheid length and ring width, there was no difference between west and east aspects in the juvenile wood. Radial, tangential shrinkage (overall and the two outermost wood strips) increased from pith outward to the bark, reaching a maximum then followed by a leveling off. Radial, tangential shrinkage (overall and the two outermost wood strips) decreased with increasing height with an exception at 0.15 m. The percentage of juvenile wood accounted for 16% and 30%, respectively, of the entire stem volume based on ring age and stem diameter as criteria. The juvenile wood zone was conical in shape. There was a strong negative correlation between juvenile wood width and cambial initial age. The values for percentage of juvenile wood volume at breast height can be used to predict the entire stem value.
Keywords: Jack pine growth; Jack pine anatomy; Radial and tangential shrinkage; Juvenile and mature wood